Modulation of small leucine-rich proteoglycans (SLRPs) expression in the mouse uterus by estradiol and progesterone - Zorn Telma MT; Favaro Rodolfo R; Salgado Renato M (BMC, 2011)
Abstract Background We have previously demonstrated that four members of the family of small leucine-rich-proteoglycans (SLRPs) of the extracellular matrix (ECM), named decorin, biglycan, lumican and fibromodulin, are deeply remodeled in mouse uterine tissues along the estrous cycle and early pregnancy. It is known that the combined action of estrogen (E2) and progesterone (P4) orchestrates the estrous cycle and prepares the endometrium for pregnancy, modulating synthesis, deposition and degradation of various molecules. Indeed, we showed that versican, another proteoglycan of the ECM, is under hormonal control in the uterine tissues. Methods E2 and/or medroxiprogesterone acetate (MPA) were used to demonstrate, by real time PCR and immunoperoxidase staining, respectively, their effects on mRNA expression and protein deposition of these SLRPs, in the uterine tissues. Results Decorin and lumican were constitutively expressed and deposited in the ECM in the absence of the ovarian hormones, whereas deposition of biglycan and fibromodulin were abolished from the uterine ECM in the non-treated group. Interestingly, ovariectomy promoted an increase in decorin, lumican and fibromodulin mRNA levels, while biglycan mRNA conspicuously decreased. Hormone replacement with E2 and/or MPA differentially modulates their expression and deposition. Conclusions The patterns of expression of these SLRPs in the uterine tissues were found to be hormone-dependent and uterine compartment-related. These results reinforce the existence of subpopulations of endometrial fibroblasts, localized into distinct functional uterine compartments, resembling the organization into basal and functional layers of the human endometrium.